Efeito do ácido giberélico e citocininas sobre a qualidade da uva apirena BRS Clara - Villar, Larissa; Terra, Maurilo Monteiro; Tecchio, Marco Antonio [UNESP]; Pires, Erasmo José Pailo; Macedo, William Rodrigues (My University, 2013)
Seedless grapes have small berries and clusters less attractive to consumers. This study aimed to evaluate the applications of synthetic cytokinins thidiazuron and forchlorfenuron, associated or not with gibberellic acid on the seedless grape cv. BRS Clara, to improve physical features of clusters and berries, in eastern São Paulo State. Two experiments were carried out in Itupeva, SP, in randomized blocks arranged in factorial 2 x 6. In the first one, gibberellic acid (0 and 20 mg.L-1) and thidiazuron (0, 2, 4, 6, 8 and 10 mg.L-1) was used and, in the second one, gibberellic acid (0 and 20 mg.L-1) and forchlorfenuron (0, 2, 4, 6, 8 and 10 mg.L-1) was used, with five replicates of two bunches per plot. The plant growth regulator solutions were applied 15 days after full bloom. After harvest, the following variables were evaluated: fresh weight, length and width of the clusters and berries, berry length/width ratio, soluble solids and titratable acidity. The use of gibberellic acid enabled improving the physical features of grapes and berries. Cytokinins applied isolated or associated with gibberellic acid did not promote changes that justify its recommendation for the evaluated conditions.

Uvas apirenas possuem bagas pequenas e cachos menos atrativos aos consumidores. Esse trabalho objetivou avaliar o efeito das aplicações das citocininas sintéticas thidiazuron e forchlorfenuron, associadas ou não ao ácido giberélico, na melhoria das características físicas de cachos e bagas do cultivar de uva apirena BRS Clara, na região leste do Estado de São Paulo. Dois experimentos foram realizados no município de Itupeva, SP, com delineamento experimental em blocos casualizados dispostos em esquema fatorial 2 x 6, sendo o primeiro ácido giberélico (0 e 20 mg.L-1) e thidiazuron (0, 2, 4, 6, 8 e 10 mg.L-1), e o segundo ácido giberélico (0 e 20 mg.L-1) e forchlorfenuron (0, 2, 4, 6, 8 e 10 mg.L-1), com cinco repetições e dois cachos por parcela. As soluções dos reguladores vegetais foram aplicadas 15 dias após o pleno orescimento. Após a colheita, foram avaliados massa fresca, comprimento e largura dos cachos e das bagas, relação comprimento/largura das bagas, sólidos solúveis e acidez titulável. A utilização do ácido giberélico, de forma isolada, possibilitou melhoria das características físicas de cachos e bagas. As citocininas aplicadas de forma isolada ou associadas ao ácido giberélico não promovem alterações que justi quem sua recomendação nas condições avaliadas.
Effect of gibberellic acid and cytokinins on the quality of BRS Clara seedless grape
Keywords: Vitis vinifera; Plant growth regulators; Physical and chemical characteristics; Vitis vinifera; Reguladores vegetais; Características físico-químicas